Penerapan Model Pembelajaran Klasikal Berbasis Bahan Alam untuk Meningkatkan Keaktifan dan Perkembangan Kognitif Anak Usia Dini - Tri Nursiamti (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
The problem in this study departs from the low focus and activeness of children in classical learning activities in kindergarten. This condition can be seen when children are easily distracted, lack enthusiasm, and passive when participating in group activities. This study aims to describe the application of classical learning based on song movement and natural material media in increasing early childhood focus and activeness. This research was carried out at Ma'arif Kindergarten by involving group B children as research subjects. The research method used is qualitative descriptive research. Data collection was carried out through observation, documentation, and brief interviews with teachers. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the application of classical learning combined with song movements and the use of natural media is able to increase children's focus and activeness. Children become more involved in learning activities, are more courageous in expressing themselves, and show higher enthusiasm. In addition, the learning atmosphere becomes more interesting and fun so as to support the achievement of learning goals optimally